2012
DOI: 10.1039/c2sc00754a
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen activation in extradiol catecholate dioxygenases – a density functional study

Abstract: Recent trapping and spectroscopic characterization of an O 2 adduct for the non-heme enzyme homoprotocatechuate 2,3-dioxygenase (HPCD) demonstrates it to be a Fe III -superoxo species. This proposal is in direct opposition to the consensus mechanism (., Proc. Natl. Acad. Sci. U. S. A., 2008, 105, 7347-7352) in which the metal facilitates the transfer of electrons from the substrate to O 2 to form the reactive species in the mechanism without changing oxidation state. In this study we performed a detailed anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
125
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(153 citation statements)
references
References 49 publications
21
125
2
5
Order By: Relevance
“…For example, differences in active site structures correlate with divergent regiospecificity and mechanisms in the intradiol and extradiol catechol oxygenases ( Figure 24) Figure 24 Proposed mechanisms for the intradiol (left) and extradiol (right) dioxygenases (adapted from [145] and [168], respectively). Similar adducts also are proposed for other members of the family of enzymes that feature the supporting 2-His-1-carboxylate facial triad as a common structural motif.…”
Section: Dioxygen Activation By Non-heme Iron Complexesmentioning
confidence: 97%
“…For example, differences in active site structures correlate with divergent regiospecificity and mechanisms in the intradiol and extradiol catechol oxygenases ( Figure 24) Figure 24 Proposed mechanisms for the intradiol (left) and extradiol (right) dioxygenases (adapted from [145] and [168], respectively). Similar adducts also are proposed for other members of the family of enzymes that feature the supporting 2-His-1-carboxylate facial triad as a common structural motif.…”
Section: Dioxygen Activation By Non-heme Iron Complexesmentioning
confidence: 97%
“…In more recent work, Neese and coworkers used a larger cluster model consisting of residues from the primary coordination sphere (H155, H214, and E267) and those in the second sphere (H200, N157, Y257, R243, and H248) that were found by crystallography to have interactions with the substrate, O 2 or the E267 ligand [54]. With this model, an earlier intermediate involving only the iron(II) center and O 2 could be found.…”
Section: Insights From Dft Calculationsmentioning
confidence: 99%
“…In the absence of metal ions, the oxidation of 1,2-dihydroxy-3-keto-5-(methylthio)pentene yields the same products as ARD′ via a base-catalyzed oxidative cleavage, indicating that dioxygen activation is not needed for enzymatic activity. 6 Other studies have shown that non-heme iron proteins, in particular non-heme iron dioxygenases, require metal activation of dioxygen, 8,9 whereas in the presence of dioxygen alone, both ARD and ARD′ do not bind oxygen, further proving the requirement of sequential binding of the substrate followed by dioxygen binding for catalysis. 6 The exact mechanisms of the two reactions remain unknown.…”
Section: +mentioning
confidence: 99%